Genomic insights from Lactiplantibacillus plantarum BRD3A isolated from Atingba, a traditional fermented rice-based beverage and analysis of its potential for probiotic and antimicrobial activity against Methicillin-resistant Staphylococcus aureus - Huidrom, Surmani; Ngashangva, Ng; Khumlianlal, Joshua; Sharma, Kongbrailatpam Chandradev; Mukherjee, Pulok Kumar; Devi, Sarangthem Indira (Frontiers in Microbiology, 2024)
Lactiplantibacillus plantarum BRD3A was isolated from Atingba, a traditional fermented rice-based beverage of Manipur. Its genomic sequence has 13 contigs and a genome size of 3,320,817 bp with a GC ratio of 44.6%. It comprises 3,185 genes including 3,112 CDSs, 73 RNAs (including 66 tRNAs and others), and CRISPR arrays. Comparative and phylogenetic analysis with the L. plantarum genome shows close similarity and about 99% average nucleotide identity. Functional annotation using EggNOG and KEGG reveals genes associated with various biological processes such as metabolism, genetic information processing, transport functions etc. Furthermore, the strain harbors bacteriocins like plantaricin E, Plantaricin F, and Enterocin X categorized under class IIb by the BAGEL4 database, indicating potential antimicrobial properties. Additionally, AntiSMASH web server predicted four secondary regions-T3PKS, Terpene, cyclic lactone inducer and RiPP suggesting higher antimicrobial potential. We validated through in vitro experiments where BRD63A exhibited promising bactericidal effects on Methicillin-resistant Staphylococcus aureus thereby inhibiting their biofilm growth. These findings indicate its potential to serve as an alternative to conventional antibiotics.